The Effects of the COVID-19 Pandemic on the Clinical Practicum of Undergraduate Nursing and Midwifery Students in Jordan: A Descriptive Survey - Rafi M. Alnjadat PhD, MSN, RN; Ahmad B. Al-Rawashdeh PhD, MSN, RN; Faizah Ayedh Almutairi RN; Mahmoud Abdel Hameed Shahin PhD, MSN, RN (SAGE Publishing, 2024)
Introduction The effects of COVID-19 lockdowns and the discontinued face-to-face clinical practicum had negative consequences on nursing and midwifery students at many levels. The clinical learning environment includes all the training and learning experiences that nursing students undergo during their clinical practicum. Objectives This study aimed to assess the effects of the COVID-19 lockdowns on the nursing and midwifery students' practicum training in governmental and private universities and academic faculties of nursing in Jordan. Methods A descriptive cross-sectional study of 1025 nursing and midwifery students from academic faculties of nursing of both governmental and private Jordanian universities was conducted in September 2021. The research group from two Jordanian universities designed and validated a 13-item survey to determine and evaluate the impact of mass lockdowns on nursing and midwifery students' practicum training. The responses were assessed using descriptive and inferential analyses. Results The findings revealed that the lockdown had a negative impact on nursing and midwifery students' self-confidence and competency in performing nursing procedures. The academic year of the students was a significant independent predictor of their self-confidence and competency levels in performing nursing procedures. Conclusion The study concluded that nursing and midwifery students were dissatisfied with their clinical education during the COVID-19 pandemic, which led to poor self-confidence in performing nursing procedures. The study group recommended repeating the clinical practicum, incorporating extensive laboratory and hospital courses, and implementing a one-year internship for newly graduated nurses and midwives to address the training gap and enhance self-confidence in clinical procedures.